The Application Of Show And Tell (S&T) Technique In Teaching Writing At MTSS AL - WASHLIYAH Serbelawan - Tiodora Fermiska Silalahi; Umi Syahyana (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2022)
The purpose of this research was to improve students‘ writing ability for Seventh Grade of MTSS AL - WASHLIYAH Serbelawan using Show and Tell (S&T) Technique.This research use Quantitative research.The design of this research is Quasi Experimental Research, with Experimental class and Controlled class. The sample of this research is 56 students of MTSS AL-WASHLIYAH Serbelawan. The researcher found the result of this research that total of pre test score in control class is 1280 with mean score is 45,36 and post test control is 1600 with mean score 57,14. While pre test in experimental class is 1340 with mean score 48,21 and post test experimental 2280 with mean 81,43. Then the researcher found that tcount (34,038) ttable (2,00404) at the significance level α0,05 with the degrees of freedom (df)55, Ho is rejected and Ha is accepted. Based on the data analysis, the researcher conducted as the following result: the population of this research is 109 students where the sample is 56 students. The result of this research of pre test score in control class is 1280 with mean score is 45,36 and post test control 1600 with mean score 57,14. While pre test in experimental class is 1340 with mean score 48,21 and post test experimental 2280 with mean 81,43. Then the researcher found that tcount (34,038) ttable (2,00404) at the significance level α0,05 with the degrees of freedom (df)55, Ho is rejected and Ha is accepted